Implementasi Program Keluarga Harapan (PKH) Dalam Meningkatkan Kesejahteraan Masyarakat Dalam Perspektif Ekonomi Syariah: Studi Di Desa Mendalo Indah, Kec. Jambi Luar Kota, Kab. Muaro Jambi, Prov. Jambi - Fadila Mawaddah; Addiarrahman Addiarrahman; Fauzan Ramli (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The Family Hope Program (PKH) is a social protection program that provides non-cash assistance to poor families designated as Beneficiary Families (KPM). PKH is a program based on poor families, so the main targets are economically disadvantaged families. PKH is an effort directed towards the formation and human resources focus on aspects of education, health, and social welfare. This research is entitled